Covid-19 e as políticas de transferências no Brasil : os impactos sobre a desigualdade de renda em 2020 - Ribeiro, Camila Oliveira (2022)
During the Covid-19 pandemic, countries established policies to mitigate the impacts of the health crisis. Brazil, in turn, implemented Emergency Aid as an exceptional transfer program to maintain income. Therefore, the objective of this dissertation is to analyze the evolution of inequality indices before and during the pandemic, observing the effects of social programs, especially Emergency Aid. Information from the Continuous National Household Sample Survey (PNADC) in the years 2012 - 2020 and the Covid-19 National Household Sample Survey (PNAD Covid-19) in 2020, both carried out by the Brazilian Institute of Geography and Statistics, were used. (IBGE). The data were organized in panel format, allowing the observation of variations and estimating inequality. The results suggest a reduction in the Gini and Palma index, indicating the importance of Emergency Aid in maintaining income during the pandemic in 2020.